If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m+m+1+m+2=57
We simplify the equation to the form, which is simple to understand
m+m+1+m+2=57
We move all terms containing m to the left and all other terms to the right.
+1m+1m+1m=+57-1-2
We simplify left and right side of the equation.
+3m=+54
We divide both sides of the equation by 3 to get m.
m=18
| 5x+3=21-4x | | 4-8x=24-4x | | x/2+14=46 | | 9x-4=5x+7 | | 8n-1=5n-10 | | 69*2-x=45 | | 6x+3=91-5x | | 10+2x=15+3x | | 86-5x=13x+16 | | z^4-8z+15=0 | | 14+5x=22+6x | | 3*3+4=16 | | p^2-13p+18=0 | | 5x-3=11x-4 | | 1-9x=55-3x | | 5x-4y=-28 | | 5x+23=10x-67 | | 5x+23=10x-68 | | 75-3x=10x-4x | | z^4-8z^2+15=0 | | 6x+12.3-10.2=1.5 | | Z-y-b= | | -p-1=-21 | | (K-p)*(r-j)= | | 3x^2-6x=x^2+x | | z+4=-4 | | m-8=-5 | | z+6=-6 | | z-7=3 | | z-7=0 | | 12+y=0 | | h/40=5 |